2022
DOI: 10.55927/eajmr.v1i7.912
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitudes, and Perceptions of Safety and Prevention Procedures among Butchers in Derna and Neighboring Areas / Libya

Abstract: This study assessed the knowledge attitude and practice of butchers in Derna City and nearby areas \ of Libya, aimed to gain Knowledge on meat handling of slaughterhouse workers in Derna, & the factors related to the knowledge, attitude and practices of slaughterhouse butchers in the Derna, Material & Methods: this was a descriptive cross-sectional study design that involved the use of quantitative methods. The study was conducted from different through personal interviews with butchers in the city of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For example, a study conducted on medical students in Iran showed that they did not receive any training on standard isolation precautions [ 35 ]. Similarly, a KAP study among butchers in Libya showed no relationship between awareness and the level of education, and even their practices in some questions [ 40 ]. In Uganda, a study revealed that there were low levels of knowledge and awareness regarding CCHF among the population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted on medical students in Iran showed that they did not receive any training on standard isolation precautions [ 35 ]. Similarly, a KAP study among butchers in Libya showed no relationship between awareness and the level of education, and even their practices in some questions [ 40 ]. In Uganda, a study revealed that there were low levels of knowledge and awareness regarding CCHF among the population.…”
Section: Discussionmentioning
confidence: 99%
“…So, health care professionals, especially family physicians, must be aware of the importance of providing comprehensive reproductive health counselling to young women, and this education should be offered to all women seen in routine screening. Additionally, this was contradicted by a study conducted in the region of Arnhem, the Netherlands, by Eljamay et al (2023) entitled "Awareness and Knowledge of Libyan Women about Endometriosis, Derna." They reported that most of the participants in their study had proper knowledge regarding signs and symptoms of endometriosis, which means that cyclic symptoms and dysmenorrhea were the most specific signs and symptoms of endometriosis.…”
Section: Assessing Awareness Of Non-medical Students At Menoufia Univ...mentioning
confidence: 98%
“…Personal hygiene is essential in reducing food contamination and foodborne illness. Transient bacteria can be transmitted through the hands and contaminated gloves (Eljamay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%